2002
DOI: 10.1238/physica.regular.066a00376
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized and Chaotic States in Dust-Contaminated Electron-Positron Magnetoplasma with Equilibrium Flows

Abstract: Nonlinear equations governing the dynamics of low-frequency (in comparison with electron gyro-frequency) electrostatic disturbances in a nonuniform resistive dust-contaminated electron-positron magnetoplasma with equilibrium sheard flow are derived. In the linear limit, a local dispersion relation has been derived and analyzed. On the other hand, in the nonlinear case, the temporal behavior of the nonlinear system can be represented in the form of a 5 × 5 matrix, which is a generalization of Lorenz-Stenflo equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[37][38][39][40][41][42] The coexistence of both DA solitons and double layers (DLs) has been studied in unmagnetized four component dusty plasma using Sagdeev's pseudopotential method. 43 Although many works have been done on nonlinear wave dynamics in e-p-dust plasmas 29,30,[44][45][46][47][48] and e-i-dust plasmas, 5,43,[49][50][51][52][53][54][55][56][57][58] however, only few studies exist on nonlinear structures in e-p-ion-dust plasmas. 59,60 In account of the ubiquitous existence of dust particulates in space and laboratory plasmas [26][27][28][29][30][31][32] and in relation with the associated observation of solitary structures, we follow the study of DA solitary waves in four components (e-p-i-d) plasma.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42] The coexistence of both DA solitons and double layers (DLs) has been studied in unmagnetized four component dusty plasma using Sagdeev's pseudopotential method. 43 Although many works have been done on nonlinear wave dynamics in e-p-dust plasmas 29,30,[44][45][46][47][48] and e-i-dust plasmas, 5,43,[49][50][51][52][53][54][55][56][57][58] however, only few studies exist on nonlinear structures in e-p-ion-dust plasmas. 59,60 In account of the ubiquitous existence of dust particulates in space and laboratory plasmas [26][27][28][29][30][31][32] and in relation with the associated observation of solitary structures, we follow the study of DA solitary waves in four components (e-p-i-d) plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the characteristics of solitons in Earth's dusty mesosphere have been examined by Popel et al [14]. Furthermore, because of the coexistence of EP pairs and dust grains in many astrophysical environment, there are some theoretical studies about nonlinear wave propagation in e-p-d plasmas, see for example [15][16][17]. It is found that the presence of charged dust grains modifies the existing plasma wave spectra and may even introduce new eigenmodes in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of the epid plasma was developed, for example, in [1][2][3][4][5][6][7]. In [1], whistlers were considered; electromagnetic surface waves were analyzed in [2], while publication [3] is devoted to the ion sound sur face of a magnetized epid plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], whistlers were considered; electromagnetic surface waves were analyzed in [2], while publication [3] is devoted to the ion sound sur face of a magnetized epid plasma. Particular cases of epid magnetoplasma in the absence of ions were described in [4,5]; chaotic behavior under low fre quency electrostatic perturbation of the plasma was con sidered in [4] and dust-acoustic waves were analyzed in [5]. Planar and nonplanar dust acoustic waves in a non magnetized epid plasma were also studied in [6].…”
Section: Introductionmentioning
confidence: 99%